Speaking Confidence in EFL Contexts: Performance Analysis of Islamic Education Students Using A Guided Monologue Template - Ramdhano, Yanri (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study explores the speaking confidence of second-semester Islamic Education students at UIN Sulthan Thaha Saifuddin Jambi through a guided monologue task supported by a structured template. A total of 40 students participated as part of their English subject coursework. Each student was asked to record a monologue introducing their personal gadget, following a sentence-based speaking guide designed to encourage structured expression and reduce speaking anxiety. The performances were evaluated based on an observation rubric consisting of six key indicators: fluency, use of fillers, eye contact, posture and body language, vocal delivery, and engagement with content. The data collected from the video recordings were analyzed descriptively by assigning scores across each category and calculating total and average scores per student. The findings indicate that most students performed confidently, with the strongest scores in vocal delivery and engagement with content. Some areas, such as posture and eye contact, showed room for improvement. Overall, the guided template helped students feel more prepared and organized in their spoken performance. The study suggests that such structured speaking activities can serve as effective tools in enhancing EFL learners’ confidence and speaking skills in higher education contexts